The Innovation and Industry 4.0: Proposal for the use of elements for a competitive organization (Research, Society and Development, 2021)
This study aims to reflect on the challenges and possibilities that the process and innovation and industry 4.0 can enhance organizational actions in corporate environments in view of the new market needs. The methodology will be through a literary survey on the subjects in focus, adding value to the discussion. A model is also proposed to guide the achievement of competitive advantage. In this sense, the authors intend to promote the subject without intending to stop it, but in order to contribute to the literature in the expansion of knowledge and in the exchange of information, adding value to organizations, assisting in organizational management as well as in specialized literature.